Beyond a Just Measure: Arendt, the ethics, the desire, and the education - Marcia Regina Fogaça (Universidade Federal do Rio Grande do Sul, 2013)
This paper intends to extract, from a psychoanalytical reading, some implications for the education of Hannah Arendt´s ideas through the Lacanian proposition of the ethic of the desire and Arendtian reflections about moral of the truth and that of the thought. For this reason, contactpoints, disjunction and resonances between Arendtian articulations and the psychoanalytical proposal, as well as some considerations are commented on the example placed by Arendt, as an alternative to the moral commandment while directed to well.